Transformation of ENSO‐related rainwater to dripwater δ18O variability by vadose water mixing - Jessica W, Moerman; Kim M, Cobb; Judson W, Partin; A Nele, Meckler; Stacy A, Carolin; Jess F, Adkins; Syria, Lejau; Jenny, Malang; Brian, Clark; Andrew Alek, Tuen (Wiley Online Library, 2014)
Speleothem oxygen isotopes (δ18O) are often used to reconstruct past rainfall δ18O variability, and thereby hydroclimate changes, in many regions of the world. However, poor constraints on the karst hydrological processes that transform rainfall signals into cave dripwater add significant uncertainty to interpretations of speleothem-based reconstructions. Here we present several 6.5 year, biweekly dripwater δ18O time series from northern Borneo and compare them to local rainfall δ18O variability. We demonstrate that vadose water mixing is the primary rainfall-to-dripwater transformation process at our site, where dripwater δ18O reflects amount-weighted rainfall δ18O integrated over the previous 3–10 months. We document large interannual dripwater δ18O variability related to the El Niño–Southern Oscillation (ENSO), with amplitudes inversely correlated to dripwater residence times. According to a simple stalagmite forward model, asymmetrical ENSO extremes produce significant offsets in stalagmite δ18O time series given different dripwater residence times. Our study highlights the utility of generating multiyear, paired time series of rainfall and dripwater δ18O to aid interpretations of stalagmite δ18O reconstructions.